Frequency and in Hospital Outcomes of Left Main Coronary Artery Disease in Patients with Acute Coronary Syndrome - Junaid, Mustafa; Khan, Adnan; Mohmand, Saad Nasir; Bacha, Sayyed Sohaib; Fatima, Aniqa (Indus Journal of Bioscience Research, 2025)
Background: Left main coronary artery (LMCA) disease in patients with Acute Coronary Syndrome (ACS) is a serious clinical entity associated with poor short-term outcomes. Despite its well-established prognostic implications, the frequency and impact of LMCA disease in ACS patients remain underexplored. Identifying demographic, clinical, and health-related factors associated with adverse outcomes is essential for improving patient management. Objective: This study aimed to evaluate the frequency of left main coronary artery disease and assess its association with in-hospital outcomes in ACS patients. Methods: A descriptive cross-sectional study was conducted involving 145 patients with ACS, including 80 with STEMI (ST-Elevation Myocardial Infarction) and 65 with non-STEMI. Baseline demographic and clinical characteristics were collected, including age, gender, comorbidities (e.g., diabetes, hypertension, dyslipidemia), and lifestyle factors (e.g., smoking). In-hospital outcomes, including arrhythmias, intra-aortic balloon pump (IABP) use, length of hospital stay, and mortality, were analyzed. Statistical associations were assessed using Chi-square tests and multivariable regression analysis. Results: The majority of patients (37.9%) were aged 60–70 years, and 55.2% were male. Comorbidities included diabetes (37.9%), hypertension (48.3%), and dyslipidemia (41.4%). STEMI was the predominant ACS type (55.2%), and 41.4% of patients experienced arrhythmias. IABP support was required in 27.6% of cases, and 10.3% of patients died. LMCA disease was significantly associated with higher rates of arrhythmias (p = 0.003), increased need for IABP (p = 0.000), longer hospital stays (p = 0.000), and higher mortality (p = 0.001). Additionally, diabetes (p = 0.004) and hypertension (p = 0.021) were also independently linked to adverse outcomes. Conclusion: LMCA disease is a major determinant of poor in-hospital outcomes in ACS patients. Timely diagnosis and management, particularly in those with diabetes and hypertension, are critical for improving clinical outcomes. Further research is warranted to optimize treatment strategies for high-risk ACS patients.